Utilizing Mansplaining as Data: Leveraging Gender and Outsider Positionalities in International Third Sector Research Fieldwork - Flanigan, Shawn Teresa (Voluntas (Manchester, England), 2023)
This article examines ways of leveraging gender and outsider positionalities in a manner that benefits the research process in international third sector field research. International research is conducted by individuals collecting data outside their country of origin or long-term residence. In the article I reflect on the role of researcher outsider status as it intersects with gender, and how these positionalities can be used to positively influence data collection in the field. I argue that aspects of female outsider status often experienced as negative also can offer unexpected benefits to research fieldwork, such as access as an outsider to conflict-affected communities, additional assistance to the “vulnerable” female, extra explanation to the “naïve” female researcher, and access facilitated by third gender or honorary male status assigned to female outsiders.